Prevalence and characterization of urinary tract infection in socially vulnerable pregnant women from Bucaramanga, Colombia - Myriam Ruiz-Rodríguez; Yuri Sánchez-Martínez; Fabio Camilo Suárez-Cadena; Jenny Carolina García-Ramírez (Revista de la Facultad de Medicina, 2021)
Introduction: Urinary tract infection (UTI) is the most common medical complication during pregnancy and is associated with adverse maternal and perinatal outcomes.